Use of steel slag as a granular material: Volume expansion prediction and usability criteria - Wang, George; Wang, Yuhong; Gao, Zhili (Journal of hazardous materials, 2010)
The theoretical equation for predicting volume expansion of steel slag is deduced based on both chemical reaction and physical changes of free lime in steel slag during the hydration process. Laboratory volume expansion testing is conducted to compare the results with the theoretical volume expansion. It is proved that they correlated well. It is furthermore experimentally proved that certain volume expansion of steel slag can be absorbed internally by the void volume in bulk steel slag under external surcharge weight making the apparent volume expansion equal zero. The minimum (lowest) absorbable void volume is approximately 7.5%, which is unrelated to the free lime content. A usability criterion is then developed based on the volume expansion of steel slag (%) and the minimum percentage of the volume that can take the volume expansion of steel slag (%). Eventually the criterion (relationship) is established based on the free lime content, the specific gravity and bulk relative gravity of a specific steel slag sample. The criteria can be used as guidance and specification for the use of steel slag and other expansion-prone nonferrous slags, copper, nickel for instance as a granular material in highway construction.